2018
DOI: 10.21511/imfi.15(1).2018.22
|View full text |Cite
|
Sign up to set email alerts
|

Managerial decisions and accounting performance following mergers in Greece

Abstract: An investigation was conducted to study a sample of 23 Greek firms listed on the Athens Stock Exchange that underwent mergers from 2011 to 2015, which is a period that embodies the Greek economic crisis. For the investigation, the authors use statistical tests to explore relative changes at twenty accounting ratios of the sample firms. These ratios are computed for one year before and after the merger. These ratios are found to be statistically insignificant indicating firms do not experience a post-merger imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 25 publications
5
13
1
Order By: Relevance
“…These results are presented in Table 4. Similar conclusions have been drawn earlier studies based on stock market or accounting performance measures that supported no significant results after mergers per industry [13,16]. On the other hand, different conclusions that there is (a) an improvement at performance in different industry than technology-intensive industrial sector were found by Pazarskis et al [1], or (b) an improvement at performance of the technology-intensive industrial sector were found by Alexandrakis et al [22].…”
Section: Intra-industry Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…These results are presented in Table 4. Similar conclusions have been drawn earlier studies based on stock market or accounting performance measures that supported no significant results after mergers per industry [13,16]. On the other hand, different conclusions that there is (a) an improvement at performance in different industry than technology-intensive industrial sector were found by Pazarskis et al [1], or (b) an improvement at performance of the technology-intensive industrial sector were found by Alexandrakis et al [22].…”
Section: Intra-industry Resultssupporting
confidence: 86%
“…There is no significant change of the examined number of the quantitative variables. Similar conclusions with no significant results after mergers per industry have been drawn earlier studies examining several accounting performance measures for the commercial and services sector after mergers [1,13]. Finally, some other researchers concluded that there is a worsening in performance [16,22].…”
Section: Intra-industry Resultssupporting
confidence: 82%
See 3 more Smart Citations